The Relationship Between Serum Electrolite Levels With Abnomality Eeg In Idiopathic And Symptomatic Epilepsy Patients - Moch Syahrial Pramudia Tarmidi; Machlusil Husna (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
Background: Electrolyte imbalances can manifest with diffuse brain dysfunction, seizure and consequently EEG abnormalities. Electrolyte disturbances is important in determining the degree of EEG abnormality. Objective: This study investigated the difference in the level serum electrolyte in idiopathic and symptomatic epilepsy. It also correlated the serum electrolyte levels with abnormality EEG. Methods: This is an observational analytical using a cross-sectional study. This study used secondary data from a medical record with inclusion and exclusion criteria patients. The subjects are all epileptic patients undergoing EEG examination at Gambiran General Hospital from June-August 2024. The subject was grouped into idiopathic and symptomatic epilepsy. The results of EEG were grouped into normal, abnormal II and III.  The examination of serum electrolyte levels was conducted on within one hour before the EEG examination. Results: We recruited 90 subjects (38 males and 52 females) were diagnosed epilepsy, 65 idiopathic and 25 symptomatic. The age 12-68 years old.  Among 90 patients, 69 had normal EEG and 21 had abnormal EEG (8 abnormal II and 13 abnormal III). Only the mean serum calcium in symptomatic epilepsy patients was higher than in the idiopathic (2,32±0,39 mmol/L vs 2,23±0,34 mmol/L). All of the mean serum electrolyte was lower in patient with abnormal EEG than the normal one. Kruskal-Wallis Correlation Test showed no significant difference between mean serum electrolyte levels with EEG result. Conclusion: There is no relationship between serum electrolyte levels with abnormality EEG in idiopathic and symptomatic epilepsy patients.